HUBUNGAN ANTARA ANEMIA DAN INDEKS MASA TUBUH IBU HAMIL TERHADAP KEJADIAN STUNTING PADA ANAK: LITERATURE REVIEW - Wahyuni, Wahyuni; Zulaikha, Fatma (Caring : Jurnal Keperawatan, 2024)
There are many factors that cause stunting, including anemia. Pregnant women who experience anemia have a reduced oxygen supply to their body cells and brain. In general, anemia in pregnant women is caused by a lack of nutrition, a lack of iron in the food consumed, poor absorption, and chronic diseases (such as tuberculosis, lung, intestinal worms, and malaria). The body mass index of pregnant women is another cause of stunting. Mothers who are short (height <150 cm) and thin (body mass index <18.5 kg/m2) have a greater risk of birthing stunting babies than mothers who have good nutritional status. In addition to macronutrient problems, micronutrient deficiencies in pregnant women need attention. The objective of this study is to determine the relationship between anaemia and body mass index of pregnant women on the incidence of stunting in children, through a literature review. We used the literature review method with 15 journals, 10 international journals, and 5 national journals. The literature review analysis revealed a correlation between anaemia and body mass index in pregnant women and the incidence of stunting. The condition of anaemia in the mother during pregnancy will affect the metabolism of the foetus to be not optimal because there is a lack of haemoglobin levels to bind oxygen so that the adequacy of nutritional intake while in the womb is low and has an impact on foetal growth, which results in low birth weight and length. There is a relationship between anemia and pregnant women's body mass index in terms of stunting incidence.